Developing a translational research framework for MDD: combining biomolecular mechanisms with a spiraling risk factor model - van Baalen, Max; van der Velden, Lars; van der Gronde, Toon; Pieters, Toine (Frontiers in Psychiatry, 2025)
ObjectiveThe global incidence and burden of Major Depressive Disorder (MDD) are increasing annually, with current antidepressant treatments proving ineffective for 30-40% of patients. Biomolecular mechanisms within the microbiota-gut-brain axis (MGBA) may significantly contribute to MDD, potentially paving the way for novel treatment approaches. However, integrating the MGBA with the psychological and environmental aspects of MDD remains challenging. This manuscript aims to: 1) investigate the underlying biomolecular mechanisms of MDD using a modeling approach, and 2) integrate this knowledge into a comprehensive ‘spiraling risk factor model’ to develop a biopsychosocial translational research framework for the prevention and treatment of MDD.MethodsFor the first aim, a systematic review (PROSPERO registration) was conducted using PubMed, Embase, and Scopus to query literature published between 2016–2020, with select additional sources. A narrative review was performed for the second aim.ResultsIn addition to genetics and neurobiology, research consistently indicates that hyperactivation of the HPA axis and a pro-inflammatory state are interrelated components of the MGBA and likely underlying mechanisms of MDD. Dysregulation of the MGBA, along with imbalances in mental and physical conditions, lifestyle factors, and pre-existing treatments, can trigger a downward spiral of stress and anxiety, potentially leading to MDD.ConclusionsMDD is not solely a brain disorder but a heterogeneous condition involving biomolecular, psychological, and environmental risk factors. Future interdisciplinary research can utilize the integrated biopsychosocial insights from this manuscript to develop more effective lifestyle-focused multimodal treatment interventions, enhance diagnosis, and stimulate early-stage prevention of MDD.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42020215412.